Develop A Long Range Drone For Wildlife Monitoring By Using Charging And Battery Replacement Pod Module - Kong, Joon Kit (Universiti Sains Malaysia, 2017)
In collaboration with the other project of developing a tricopter drone, the purpose of this project is to develop a long range drone by using charging and battery replacement pod module so that the drone is capable to fly over a long range for a long period to monitor the wildlife in the areas that are hardly reachable such as rainforest as there are dense growth of trees and tangled growth of vines and shrubs on the ground. This project will be focusing on the development the pod module. The design in this project is based on the features and specifications of the tricopter. The pod module is developed for the drone to replenish its battery autonomously. The mechanism of the pod module is controlled by using a direct current motor (DC motor) mounted with a lead screw to push and pull the battery slots along the pod module for battery swapping purpose. Two limit switches are used to control the movements of the battery slots. The DC motor and the limit switches are controlled by using MATLAB Simulink and programming the Arduino Uno Board which is connected to them. As an idea for wildlife monitoring, a few stations for charging and battery replacement can be placed in the desired area to ensure a long range flight of the drone. First, the Tricopter was designed so that it can land on the battery changing platform which the landing gears are framed to meet the platform design as the drone has to be in a fixed position for battery replacement after landing.